2023
DOI: 10.32509/jakpi.v2i1.1992
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tindakan Investasi Infrastruktur dan Pelayanan Terhadap Masyarakat Serta Kepemilikan Institusional Terhadap Profitabilitas

Abstract: This research objective was to analyze the impact of infrastructure investment actions on the community and institutional ownership on the profitability of mining companies listed on the IDX from 2017 to 2019. The research method was descriptive quantitative with panel data regression analysis on 18 mining companies listed on the IDX data time. The series is data for the period 2017 to 2019. The results concluded that there was a significant relationship between infrastructure investment actions and services p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…When corporations use debt to its best advantage, they can produce strong long-term growth, which in return rewards investors. This is consistent with significance theory, that holds that consistent profitability significance investors in a good way, so promoting further investment and raising the value of the company (Giawan, 2023). Previous study has indicated that capital structure positively affects the value of a company (Adnyani & Suaryana, 2020…”
Section: H1: Managerial Ownership Has a Positive Effect On Company Valuesupporting
confidence: 86%
See 1 more Smart Citation
“…When corporations use debt to its best advantage, they can produce strong long-term growth, which in return rewards investors. This is consistent with significance theory, that holds that consistent profitability significance investors in a good way, so promoting further investment and raising the value of the company (Giawan, 2023). Previous study has indicated that capital structure positively affects the value of a company (Adnyani & Suaryana, 2020…”
Section: H1: Managerial Ownership Has a Positive Effect On Company Valuesupporting
confidence: 86%
“…Enhanced profitability also stimulates market response, as more investors are attracted to the company. This, in turn, directly elevates the company's value, reflected in increased share prices (Giawan, 2023) This means that the company can attract the attention of investors by increasing the company's profits, thereby safeguarding against declines and potential bankruptcy. This research conducted by (Antoro et…”
Section: The Effect Of Profitability On Company Valuementioning
confidence: 99%